THE GLOBAL COMPETITIVENESS OF ARAB ECONOMIES - TRENDS AND CHALLENGES (International Journal of Engineering Sciences & Management Research, 2021)
This research is summarized in identifying the nature of competitiveness as a concept, goal and mechanisms as an important means for the success of countries and raising their growth rates and indicators and the ability of Arab economies to work within the framework of their requirements and their ability to provide the requirements of global competitiveness that formed part of the research problem. The research included several investigations describing the status of these economies and through this research, we have reached several results, the most important of which indicate improvement in most of the main sectors of the economy indicators in some Arab countries, especially the Gulf, while other Arab countries witnessed a relative decline in most of these indicators. With the deterioration of the relative situation in the field of the business environment as a result of the delayed administrative and regulatory apparatus, the rigidity of laws and the spread of administrative corruption, which impedes investment. The research also came up with some proposals, the most important of which was the need to improve the competitiveness of the Arab industry at the global level to achieve real growth indicators and contribute to economic well-being through the approved economic openness. Foreign trade and foreign direct investment should be linked to raising competitiveness indicators by adopting advanced strategies for competitiveness in an international economic environment characterized by intense competition by ensuring product quality in order to compete with products of other countries.